2015
DOI: 10.1515/bmt-2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

Femoral cement extraction in revision total hip arthroplasty – an in vitro study comparing computer-assisted freehand-navigated cement removal to conventional cement extraction

Abstract: The freehand-navigated cement removal, with the exception of the preparatory examinations, is time saving compared to the conventional method. However, a potential for technical development especially for the milling device and accuracy exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Therefore, subsidence might be associated with incomplete cement mantle removal or endosteal ischemia due to cementation during primary stem fixation. Mumme et al 18) reported that there is still some difficulty in achieving complete removal of a residual well-fixed cement mantle, showing a mean value of 1.6 ± 0.4 mm with conventional methods. 19) These remnants of the cement mantle in the intramedullary canal may interrupt on-growth on the stem surface.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, subsidence might be associated with incomplete cement mantle removal or endosteal ischemia due to cementation during primary stem fixation. Mumme et al 18) reported that there is still some difficulty in achieving complete removal of a residual well-fixed cement mantle, showing a mean value of 1.6 ± 0.4 mm with conventional methods. 19) These remnants of the cement mantle in the intramedullary canal may interrupt on-growth on the stem surface.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction techniques of well-fixed cemented or uncemented RTKA implants can be challenging and are linked with increased risks for complication [40][41][42][43][44][45][46][47]. Ultrasonic methods [48], pneumatic shock wave technology and intramedullary endoscopy (mostly for hip procedures but also for the knee) [49,50] customized guides [51], highpowered drills with centralizers [52], and computer assisted freehand navigations [53] are new technologies and methods for implant removal in revision total knee and hip arthroplasties that aim to reduce complication risks and possibly the need for osteotomies. However, due to several limitations and still missing reliable evidence for the superiority of one or another method, these techniques rely mostly on the individual preference of the surgeon and have not gained enough acceptance until now to prevail on the daily praxis in RTKA.…”
Section: Discussionmentioning
confidence: 99%
“…Biplanar setup fluoroscopically guided cement removal in revision total hip arthroplasty have lowered the risk of intraoperative bone injury [10]. A recent publication reported on a new computer-assisted 3D navigation in a reconstruction model [11]. However, studies on the use of conventional cement extraction techniques and employing computed imaging were unable to demonstrate that this resulted in significantly shorter operating times [11,19].…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication reported on a new computer-assisted 3D navigation in a reconstruction model [11]. However, studies on the use of conventional cement extraction techniques and employing computed imaging were unable to demonstrate that this resulted in significantly shorter operating times [11,19]. This may be due to the fact that repeated image converter adjustment under sterile conditions and the poor view in the medullary cavity of the bone all require significant operating time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation